Mo doped porous Ni–Cu alloy as cathode for hydrogen evolution reaction in alkaline solution. Issue 100 (29th October 2015) - Yu, Linping; Lei, Ting; Nan, Bo; Kang, Jiangang; Jiang, Yao; He, Yuehui; Liu, C. T.
<x xml:space="preserve">Abstract</x> Molybdenum doped porous Ni–Cu cathodes are conveniently prepared by powder metallurgy in this work.